Memória afetiva & ações físicas: apropriações do teatro ao cinema (Olhares, 2019)
This article analyzes the origin of the exercise of “affective memory” in the work of the actor, from the perspective of K. Stanislavski, Lee Strasberg’s appropriations in the Actors Studio, and their possible applications in theater and film.
Keywords: Acting; Affective memory; Stanislavski; Lee Strasberg